2010
DOI: 10.1002/prot.22667
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for regulation of poly‐SUMO chain by a SUMO‐like domain of Nip45

Abstract: Post-translational modification by small ubiquitin-like modifier (SUMO) provides an important regulatory mechanism in diverse cellular processes. Modification of SUMO has been shown to target proteins involved in systems ranging from DNA repair pathways to the ubiquitin-proteasome degradation system by the action of SUMO-targeted ubiquitin ligases (STUbLs). STUbLs recognize target proteins modified with a poly-SUMO chain through their SUMO-interacting motifs (SIMs). STUbLs are also associated with RENi family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…The only other proteins known to interact with the N-terminus of UBC9 are the Rad60 family members. These proteins bind UBC9 by large integral SUMO-like domains, which adopt a b-grasp fold similar to SUMO; these interactions promote cellular responses to genotoxic stress (Prudden et al, 2009;Sekiyama et al, 2009). Our discovery that the short linear MoRF EVIDLT in E1A recapitulates this interaction is unprecedented.…”
Section: Discussionmentioning
confidence: 92%
“…The only other proteins known to interact with the N-terminus of UBC9 are the Rad60 family members. These proteins bind UBC9 by large integral SUMO-like domains, which adopt a b-grasp fold similar to SUMO; these interactions promote cellular responses to genotoxic stress (Prudden et al, 2009;Sekiyama et al, 2009). Our discovery that the short linear MoRF EVIDLT in E1A recapitulates this interaction is unprecedented.…”
Section: Discussionmentioning
confidence: 92%
“…All of these proteins share two tandem SUMO-like domains (SLD1 and SLD2). Structural and biochemical analysis of RENi SLDs revealed that these domains are unable to bind to class I SIMs but SLD2 interacts with the backside of Ubc9 by mimicking the β-sheet required for this class II SUMO interaction (136,137). Of note, RENi proteins also contain a conserved SIM in their N-termini and bind to SUMO, but they are themselves inefficient sumoylation substrates (138)(139)(140).…”
Section: E2 Regulationmentioning
confidence: 99%
“…Structure-based in vitro studies have suggested a role for a noncovalent complex formed by Ubc9 and SUMO (Ubc9:SUMO) in SUMO polymerization; however, in vivo evidence for such a function is lacking (9,15,22,48). It is also unclear whether the observed binding of Rad60 SLD2 to Ubc9 (39) antagonizes SUMO chain formation by disrupting the Ubc9:SUMO complex (42). In addition, whether the major SUMO E3 ligase Pli1 and its homologs Siz1/Siz2 of budding yeast and PIAS (protein inhibitor of activated STAT)-type ligases of higher eukaryotes (51) play a key role in forming SUMO chains remains unanswered.…”
mentioning
confidence: 99%